2014
DOI: 10.1161/circep.114.001612
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Predictors of Lead Conductor Fracture

Abstract: All 23 adult Canadian implantable cardioverter defibrillator implantation centers were surveyed to identify centers that routinely capture anteroposterior or posteroanterior (AP) and lateral x-rays within 2 weeks of implant and at least AP x-rays at the time of fracture identification. Eight of those centers collected those x-rays routinely. All eligible centers agreed to participate in the study. Centers were © 2014 American Heart Association, Inc. Original ArticleBackground-Lead fracture is a limiting facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…Instead, the use of body surface of the second rib as landmark offered a significantly higher (100 %) success rate and a more lateral approach avoiding potential lead entrapment between the clavicle and the first rib, a cause of lead failure during follow-up [10]. Recently, Krahn, in a retrospective case-control study of 133 patients with Fidelis lead fractures, found that a more lateral vein access point is associated with a lower fracture risk [27]. In our study, in four or five patients with a Bfirst rib approach^failure due to abnormal vein course, the venography showed that axillary vein crossed the body surface of the second rib.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the use of body surface of the second rib as landmark offered a significantly higher (100 %) success rate and a more lateral approach avoiding potential lead entrapment between the clavicle and the first rib, a cause of lead failure during follow-up [10]. Recently, Krahn, in a retrospective case-control study of 133 patients with Fidelis lead fractures, found that a more lateral vein access point is associated with a lower fracture risk [27]. In our study, in four or five patients with a Bfirst rib approach^failure due to abnormal vein course, the venography showed that axillary vein crossed the body surface of the second rib.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of subclavian crush syndrome can also be predicted by several angiographic parameters, such as pocket, intravascular and intracardiac lead characteristics [ 10 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in using the PA approach to puncture the subclavian vein over the first rib, many operators will chose a steep angle (perpendicular to the chest wall) to minimise any drift in the superior/inferior directions, which could lead to a puncture beyond the boundaries of the first rib and hence a pneumothorax. However, accessing the subclavian vein at a perpendicular angle can theoretically increase flexion stress on the lead 6. The caudal view improves visualisation of the first rib and lung borders (figure 1C) and permits a shallower angle of entry into the subclavian vein theoretically reducing the risk of flexion damage to the lead.…”
Section: Discussionmentioning
confidence: 99%